2008
DOI: 10.1677/joe-08-0166
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of norethisterone, a progesterone receptor agonist into estrogen receptor agonists in osteoblastic cells

Abstract: A number of clinical studies have demonstrated that norethisterone (NET), a potent synthetic progestin, restores postmenopausal bone loss, although its mode of action on bone cells is not fully understood, while the effect of naturally occurring progesterone in bone has remained controversial. A recent report claims that the potent effects of NET on osteoblastic cell proliferation and differentiation, mimicking the action of estrogens, are mediated by non-phenolic NET derivatives. To determine whether osteobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
1
7
0
6
Order By: Relevance
“…Meanwhile, an almost complete absence of diols was noticed when radiolabeled T was incubated with rat osteoblasts in the presence of Flu, an inhibitor of 3 α -and 3 β -hydroxysteroid dehydrogenases. These findings are in line with previous reports from our group, demonstrating that norethisterone (NET), a synthetic progestin derived from 19-nortestosterone, was bioconverted in neonatal rat osteoblasts to the A-ring-reduced metabolites 5 α -dihydro-NET and 3 α -and 3 β -tetrahydro-NET [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, an almost complete absence of diols was noticed when radiolabeled T was incubated with rat osteoblasts in the presence of Flu, an inhibitor of 3 α -and 3 β -hydroxysteroid dehydrogenases. These findings are in line with previous reports from our group, demonstrating that norethisterone (NET), a synthetic progestin derived from 19-nortestosterone, was bioconverted in neonatal rat osteoblasts to the A-ring-reduced metabolites 5 α -dihydro-NET and 3 α -and 3 β -tetrahydro-NET [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…cDNA samples were subjected to quantitative amplifi cation using the TaqMan probe and primers set of Alp 1 (Rn01516026_ml) as previously described [ 40 ]. Gene expression was normalized against β -actin used as a housekeeping gene.…”
Section: Isolation Of Total Rna and Real-time Pcrmentioning
confidence: 99%
“…The relative binding affinity of 2-OHE 1 and 2-OHE 2 to cytosolic ER was assessed using a competition analysis, as previously described by our group [31], using progesterone (P) and E 2 as the controls. Cytosol aliquots (200 µg protein/ml) were incubated with 1 nM [ 3 H]-E 2 at 4 °C for 18 h in the absence or presence of increasing concentrations (1, 5, 10, 100 and 250 nM) of the radio-inert steroids E 2 , P, 2-OHE 1 and 2-OHE 2 .…”
Section: Competition Studiesmentioning
confidence: 99%
“…Similarly, progesterone, which was used as the negative control, was unable to compete for binding to ER. The inhibition constant (K i ) was calculated for each competitor using K d = 1.19 × 10 −9 M, as previously described in a study by our group that was aimed at characterizing the kinetic constants, at equilibrium, of ER using [ 3 H]-E 2 [31]. The RBA and K i values of each steroid competitor are listed in Table 1.…”
Section: Estrogen Receptor Bindingmentioning
confidence: 99%
“…Whether progestins bind to the ER is contradictory. Some studies suggest that medroxyprogesterone acetate (MPA) and norethisterone (NET) can bind to the ER and elicit estrogenic activity, others suggest that they do not (Larrea et al 2001, Pasapera et al 2002, Escande et al 2006, Lemus et al 2009. Interestingly, we recently showed that NET-acetate (NET-A), levonorgestrel (LNG) and gestodene (GES) can bind to ER-A, but not ER-B, while P 4 , MPA, nestorone (NES), nomegestrol acetate (NoMAC) and drospirenone (DRSP) do not bind to either ER subtype (Louw-du Toit et al 2017).…”
Section: Introductionmentioning
confidence: 99%